Manufatura aditiva a laser e fusão a arco da liga Ti-15Nb de baixo módulo de elasticidade para aplicações biomédicas - Mattos, Felype Narciso de (Universidade Federal de São Carlos, 2023)
Ti alloys are acclaimed for biomedical applications due to their excellent mechanical, biocompatibility and corrosion resistance properties. Based on these characteristics, pure Ti and different Ti alloys have been applied in the biomedical industry, especially the Ti-6Al-4V (wt %) alloy. However, although it presents good mechanical properties, this alloy presents problems regarding cytotoxicity of Al and V elements related to neural disorders such as Alzheimer's disease. Furthermore, for orthopedic applications, there is a considerable difference among elastic modulus of Ti and α+β alloys, from E = 100 to 110 GPa, and that of human bone, around E = 30 GPa. This property mismatch leads to stress shielding phenomenon, which is not desirable since it can promote loss of bone density and consequently diseases as osteopenia and osteoporosis. In this context the Ti-15Nb alloy emerge and was produced by selective laser melting (LPBF) and vacuum arc melting as an alternative to Ti 6Al-4V since it is free of toxic elements and presents an elastic modulus nearer human bone. The stablished phases were identified by the X-ray diffraction technique and in the AC, RR, LQ and LPBF samples the found phases were α' + β, while in the RL sample the phases identified were α + β and all these phases were confirmed by microscopy techniques. Elastic modulus and hardness were measured by impulse excitation and Vickers microhardness techniques, varying their values from 56 to 88 GPa and 236 to 500 HV. Yet, for additive manufacturing, it was possible to stablish an operational window of 130 to 150 J/mm³. In this way, low levels of porosity and un-melted Nb are obtained.
Laser additive manufacturing and arc melting of low modulus Ti-15Nb alloy for biomedical applications
Keywords: Ligas Ti; Ti-15Nb; LPBF in-situ alloying; Baixo módulo de elasticidade; Ti alloys; Low elastic modulus; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA